2022
DOI: 10.1111/jcmm.17171
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis‐related gene NOX4, CHAC1 and HIF1A are valid biomarkers for stomach adenocarcinoma

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(20 citation statements)
references
References 31 publications
1
19
0
Order By: Relevance
“…Moreover, the typical features of ferroptosis include the inactivation of defensive GPX4 and the enhanced expression of the key protein ACSL4 during the formation of polyunsaturated-fatty-acid-containing phospholipids (PUFA-PLs). 38,39 Similar protein expression trends are shown in Fig. 5E, especially in the Simva-HMPB-Mn@GOx group.…”
Section: Resultssupporting
confidence: 66%
“…Moreover, the typical features of ferroptosis include the inactivation of defensive GPX4 and the enhanced expression of the key protein ACSL4 during the formation of polyunsaturated-fatty-acid-containing phospholipids (PUFA-PLs). 38,39 Similar protein expression trends are shown in Fig. 5E, especially in the Simva-HMPB-Mn@GOx group.…”
Section: Resultssupporting
confidence: 66%
“…CHAC1, ChaC Glutathione Specific Gamma-Glutamylcyclotransferase 1, is a protein-coding gene. CHAC1 was reported to be a ferroptosis-related gene, and mainly explored in various cancers [ 40 42 ], while no related finding was reported in stroke disease. The research focus on miR-760-3p was rare, and only one study reported that it was related to inflammatory [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…[33] CHAC1 is a ferroptosis-related gene, and its increased expression indicates an increased risk of cancer recurrence in patients with breast and gastric cancer. [34,35] TRIB3 reduces CD8 T cell infiltration and induces immune escape by inhibiting the STAT1-CXCL10 axis in colorectal cancer. [36] TRIB3 promotes the development of MYC-associated lymphoma by inhibiting UBE3B-mediated degradation of MYC.…”
Section: Discussionmentioning
confidence: 99%